AWS SysOps Cookbook - Second Edition - Beard, Eric; Udell, Rowan; Chan, Lucas (Packt Publishing, 2019)
Become an AWS SysOps administrator and explore best practices to maintain a well-architected, resilient, and secure AWS environment Key Features Explore AWS Cloud functionalities through a recipe-based approach Get to grips with a variety of techniques for automating your infrastructure Discover industry-proven best practices for architecting reliable and efficient workloads Book Description AWS is an on-demand remote computing service providing cloud infrastructure over the internet with storage, bandwidth, and customized support for APIs. This updated second edition will help you implement these services and efficiently administer your AWS environment. You will start with the AWS fundamentals and then understand how to manage multiple accounts before setting up consolidated billing. The book will assist you in setting up reliable and fast hosting for static websites, sharing data between running instances and backing up data for compliance. By understanding how to use compute service, you will also discover how to achieve quick and consistent instance provisioning. You'll then learn to provision storage volumes and autoscale an app server. Next, you'll explore serverless development with AWS Lambda, and gain insights into using networking and database services such as Amazon Neptune. The later chapters will focus on management tools like AWS CloudFormation, and how to secure your cloud resources and estimate costs for your infrastructure. Finally, you'll use the AWS well-architected framework to conduct a technology baseline review self-assessment and identify critical areas for improvement in the management and operation of your cloud-based workloads. By the end of this book, you'll have the skills to effectively administer your AWS environment. What you will learn Secure your account by creating IAM users and avoiding the use of the root login Simplify the creation of a multi-account landing zone using AWS Control Tower Master Amazon S3 for unlimited, cost-efficient storage of data Explore a variety of compute resources on the AWS Cloud, such as EC2 and AWS Lambda Configure secure networks using Amazon VPC, access control lists, and security groups Estimate your monthly bill by using cost estimation tools Learn to host a website with Amazon Route 53, Amazon CloudFront, and S3 Who this book is for If you are an administrator, DevOps engineer, or an IT professional interested in exploring administrative tasks on the AWS Cloud, then this book ...